Concepções dos(as) professores(as) de química sobre o desenvolvimento de competências na escola - Verônica T. Santos; Angela F. Campos; Maria Angela V. de Almeida (Ensaio Pesquisa em Educação em Ciências, 2005)
This paper reports a research carried out chemistry teachers group of high school education in order to investigate as they conceive the approaching by competencies in the school. The methodology involved the following stages: conceptions of the teachers about competence, using as research instrument a questionnaire; it analyses and validation of the answers of the teachers to the questionnaire; discussion about competence in the school, using as instruments a Perrenoud's text and video. The results showed that there is not mobilization of the teachers and schools to relation with approaching of competencies. Besides that, this approaching will be possible if the educational system to be concerned salary best, recourses, available time and a continued formation introduced in the school pedagogical project, that propitiate the cooperation between teachers and university and contribute to the discussion about chemistry subjects, methodology and evaluation. And, the same time, the construction of the news professional competencies in the teachers.